THE INFLUENCE OF THE CADETS’ BODY MASS ON THEIR PULL-UP RESULTS (Physical Culture and Sport: Scientific Perspective, 2025)
The study aimed to determine the effect of cadets’ body weight on the results of pull-ups and to develop a formula for estimating the number of pull-ups depending on body weight. The research methods were as follows: theoretical analysis and generalization, pedagogical experiment, anthropometry, and statistics. Results. The examination of 30 cadets of the National Defence University of Ukraine included recording the following cadets’ measurements: age, height, body weight, pull-ups and hand grenade distance throwing. The data analysis revealed that the coefficient of variation of pull-ups (V=29.8%) indicates heterogeneity of results. The average number of pull-ups is 14, which is estimated at 85 points on a 100-point scale. The relative pull-up ratio is the ratio of the number of pull-ups to body weight. The correlation coefficients showed no statistical relationship between pull-ups and hand grenade throwing (r =0.136), a low relationship between body weight and agе (r=0.377), average relationship between body weight and height (r=0.483), strong relationship between body weight and body constitution (r=0.722); negative correlation between the number of pull-ups and body weight (r=- 0.643), which confirms a decrease in performance with increasing weight. Conclusions. The relative pull-up coefficient is proposed, which can be used to assess cadets’ physical fitness. It was found that in 80% of cases (n=30), the pull-up results of the cadets improved with the normalization of their body weight. For 40% of cadets, this is quite enough to fulfill the standard for excellent marks. In addition to body weight regulation, the rest of the cadets need to pay attention to increasing their fitness in this exercise. It has been determined that the results obtained can be used to improve the methods of physical training of military personnel, in particular, to adjust the standards in pulling up, taking into account body weight, and developing individual physical training programs.
Keywords: cadets; correlation coefficient; coefficient of variation; body weight; pull-ups; analysis